2014
DOI: 10.1155/2014/182981
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Sex Reassignment Surgery in Thailand: A Social Perspective

Abstract: This paper reviews the development of gender reassignment in Thailand during the period of 1975–2012, in terms of social attitude, epidemiology, surgical patients' profile, law and regulation, religion, and patients' path from psychiatric assessment to surgery. Thailand healthcare for transsexual patients is described. Figures related to the number of sex reassignment surgeries performed in Thailand over the past 30 years are reported. Transsexual individuals are only apparently integrated within the Thail soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…This usually involves the use of an estrogen and anti‐androgen concomitantly. In a cross‐sectional sample of TGW in Thailand, approximately 75% reported using FHT for a mean duration of 10 years . Many TGW used higher‐than‐recommended doses and 50% reported symptoms from these higher doses of oral contraceptive pills .…”
Section: Introductionmentioning
confidence: 99%
“…This usually involves the use of an estrogen and anti‐androgen concomitantly. In a cross‐sectional sample of TGW in Thailand, approximately 75% reported using FHT for a mean duration of 10 years . Many TGW used higher‐than‐recommended doses and 50% reported symptoms from these higher doses of oral contraceptive pills .…”
Section: Introductionmentioning
confidence: 99%
“…For the best possible care, information regarding irreversible physical changes should be provided before the initiation of treatment [ 1 ]. Studies have shown that almost all Thai transsexuals self-medicate with hormonal therapy that includes hormones that are usually bought directly from the pharmacy without any prescription; therefore, transwomen are not warned about the loss of reproductive function [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transgender men and women are unable to enter a heterosexual marriage under existing marriage legislation or to have related rights and benefits. Transgender people, including those who have undergone gender-affirming surgery, also cannot legally change their personal title or legal sex on state documents (Chokrungvaranont et al 2014). Intersex individuals may change their legal sex after gender affirming surgery, provided they have documentation from a health care provider certifying their original legal sex had been incorrectly assigned (iLaw 2012).…”
Section: Resultsmentioning
confidence: 99%